The Five Bai’at of the Sheikh Musthafa Husein: Contextualization of National Values in the Current Era - Faisal Musa; Datuk Imam Marzuki; Susanti Hasibuan (KURAS Institute, 2025)
This study explores the meaning of the bai’at of Sheikh Mustafa Husein and relates it to the contemporary context at Pesantren Musthafawiyah Purba Baru. The research employs a qualitative approach using functional theory, which views society as a system consisting of interconnected parts that work together to maintain the stability and balance of the whole. This theory was developed by sociologists Émile Durkheim, Talcott Parsons, and Robert K. Merton. The content of the bai’at emphasizes commitments such as refraining from adultery, not taking human life, avoiding immoral acts, worshiping none other than Allah forever, and pledging not to betray the homeland and religion until the end of time. In relation to the present context, this bai’at is effective in fostering a spirit of nationalism among the santri. They continue to uphold their dignity in interactions with non-mahram individuals, exercise patience to avoid conflict, and preserve the purity of their monotheistic faith in Allah, affirming Him as the one and only God on earth.